A model for the quaternary structure of human placental insulin receptor deduced from electron microscopy. - Christiansen, K (1991)
Electrophoretically pure and functionally intact human placental insulin receptor was studied by electron microscopy with negative-staining techniques. The quaternary structure of the detergent-solubilized receptor was determined. The receptor had the shape of a letter T approximately 24 nm in height and 18 nm in width with a thickness of the stem and the crossbar of 3-4 nm. No consistent change in ultrastructure of the receptor could be detected after the addition of insulin alone or insulin and Mn2+/Mg2+/ATP. After partial reduction of the alpha 2 beta 2 heterotetrameric receptor into alpha beta heterodimers, the electron micrographs showed a clear reduction in average size of the molecule with disappearance of the T profiles characteristic of the alpha 2 beta 2 heterotetramers. By incubation of the heterodimers in a phosphorylation medium containing insulin, a reassociation to molecules with molecular weights of the alpha 2 beta 2 heterotetramer took place judged from SDS/PAGE. Electron microscopy showed that the molecule formed larger aggregates, and only a few solitary T-shaped copies were seen.